1998
DOI: 10.2176/nmc.38.suppl_146
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal Nerve and Brainstem Catecholamine Systems in Cerebral Vasospasm

Abstract: Cisternal blood injection in the rat and squirrel monkey produces a biphasic cerebral vasospasm, a decrease in cerebral blood flow (CBF) and an increase in glucose uptake (CMRglu) due to an anaerobic glucolysis actually representing a decrease in metabolism. Lesioning of the A2-nucleus, its ascending cathecolamine pathways or their projection site, the median eminence in the hypothalamus, prevents the occurrence of spasm. A unilateral postganglionic trigeminal lesion causes an ipsilateral constriction of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Another study, however, showed that glucose uptake increased by as much as 250% when measured 48 h after cisternal injection (Delgado et al, 1986a). This SAH-induced increase in glucose utilization was confirmed in a report by Svendgaard et al (1998) in which both rats and monkeys were studied. However, when investigators addressed mitochondrial oxidative capacity using cytochrome oxidase histochemistry, they reported that some regions of the brain exhibited an acute decrease followed by a late (72 h) increase in reactivity (Marzatico et al, 1988(Marzatico et al, , 1990.…”
Section: Introduction T He Events Follow Ing a Subarachnoid Hemorrhagesupporting
confidence: 59%
“…Another study, however, showed that glucose uptake increased by as much as 250% when measured 48 h after cisternal injection (Delgado et al, 1986a). This SAH-induced increase in glucose utilization was confirmed in a report by Svendgaard et al (1998) in which both rats and monkeys were studied. However, when investigators addressed mitochondrial oxidative capacity using cytochrome oxidase histochemistry, they reported that some regions of the brain exhibited an acute decrease followed by a late (72 h) increase in reactivity (Marzatico et al, 1988(Marzatico et al, , 1990.…”
Section: Introduction T He Events Follow Ing a Subarachnoid Hemorrhagesupporting
confidence: 59%
“…For example, animal models of SAH have demonstrated the importance of pontine adrenergic pathways projecting to the median eminence as well as trigeminal nerve afferents innervating intracranial blood vessels in producing vasospasm [12,[21][22][23][24][25]. However, in a cat model of SAH, it was demonstrated that the sympathetic overactivity was triggered by elevated ICP [26].…”
Section: Discussionmentioning
confidence: 99%
“…[71617] It is widely believed that blood, or its degradation products, causes vasospasm by directly affecting the walls of the cerebral arteries. [29] The pathogenesis of the arterial narrowing that occurs following a SAH is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…[91128] Unilateral postganglionic trigeminal lesions result in ipsilateral constriction of the cerebral arteries and consequent decrease of the CBF; however, pre-ganglionic lesions do not affect the baseline diameter of cerebral arteries. [2629]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation